Are boards 'substitute' or 'complement' dividend payout? Econometric evidence for Indian banks. (7th January 2022) - Bhatia, Madhur; Gulati, Rachita
Abstract: This study econometrically tests the 'substitution' versus 'outcome' hypotheses by examining the impact of board governance on the dividend payout policy in the Indian banking industry. The analysis is confined to the period from 2005 to 2018. The results reveal a significant positive influence of overall board quality on the magnitude of payouts, supporting the 'outcome hypothesis'. At the disaggregated level, independent directors, female directors, chief executive officer duality, and board meetings significantly influence the dividend policy of Indian banks. Our further investigation of the board‐dividend nexus at the ownership level shows that this complement relation is only visible in private banks (PBs). While the 'substitution hypothesis' holds in public sector banks (PSBs). The results suggest that good governed PBs use dividends as a complementary measure of monitoring mechanism. In contrast, governed boards of PSBs take conservative financial decisions and declare a low dividend. The findings are robust at disaggregate level, corroborating our main findings and additional analyses, including propensity score matching depicting that our conclusions are not beset by endogeneity or selection bias.